Low carbon transport strategy in Europe: A critical review. Issue 1 (2nd January 2017) - Emberger, Guenter
ABSTRACT: The purposes of this article are to depict ongoing trends regarding the transport system in Europe, to introduce readers to the challenges that Europe (and the rest of the world) will face in the future, to show which strategies Europe plans to deploy to mitigate the negative impacts the transport system imposes on the overall system, and finally to discuss the potential of these suggested strategies to contribute to the objectives of the European Union in the long run.